Penyuluhan Kesehatan dan Pemeriksaan Kadar Asam Urat pada Masyarakat di Jungsereh Garut - Lia Mar’atiningsih; Sugiah Sugiah; Muhammad Hadi Sulhan; Gina Nafsa Mutmaina; Mamay Mamay; Astari Nurisani; Meti Rizki Utari; N.Ai Erlinawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Hyperuricemia is defined as increased levels of uric acid in the blood, this can result in gout which is characterized by pain and redness in the joints. Currently, increased uric acid levels are often caused by excessive consumption of red meat including offal, being overweight, consuming foods high in cholesterol, and rarely exercising. The purpose of this counseling and examination of uric acid levels is to increase public knowledge about gout and gout screening by conducting uric acid examinations using POCT. The implementation method used is direct delivery of material related to gout, symptoms, and prevention including screening of uric acid examinations using the POCT method.